A Geochemical Comparison of Three Terrestrial Sites of Serpentinization: The Tablelands, the Cedars, and Aqua de Ney. Issue 11 (1st November 2021) - Cook, Melissa C.; Blank, Jennifer G.; Rietze, Amanda; Suzuki, Shino; Nealson, Kenneth H.; Morrill, Penny L.
Abstract: Although the Earth's subsurface hosts an abundance of microbial life, the influence of geochemistry on these communities remains poorly constrained. Ophiolites, sites where oceanic ultramafic minerals can be hydrated to serpentine minerals and metal oxides, create unique conditions capable of sustaining life. The fluid geochemistry of the Tablelands (NL, CAN), The Cedars (CA, USA), and Aqua de Ney (CA, USA), were studied to better characterize the range of fluid compositions observed at terrestrial sites of serpentinization. Fluids from these sites shared many commonalities including being ultra‐basic and reducing as well as having elevated levels of Cl −, Na +, K +, and Br − and depleted concentrations of Mg 2+ . They also exhibited a wide range of geochemistry. Isotopic and compositional data suggested the CH4 from The Cedars was a mixture of microbial and non‐microbial sources while the CH4 from the Tablelands was non‐microbial in origin. Aqua de Ney was the only site where the CH4 plotted in the abiogenic field. Despite being a known product of serpentinization, no H2 was detected at Aqua de Ney, likely due to the formation of abiogenic CH4 as well as the reaction of H2 and SO4 2− in the system to produce H2 S. These unique sites of terrestrial serpentinization help to better understand the range of geochemistry at sites of serpentinization and its influence on the microbial communities in the subsurface. Plain Language Summary: The subsurface of the Earth hosts an abundance of life; however, little remains known about the conditions that support life in the groundwater system of ultramafic rocks (i.e., rocks rich in iron and magnesium). Three contrasting sites (the Tablelands, The Cedars, and Aqua de Ney) were chosen to expand the knowledge of how the range of geochemistry that exists between sites of serpentinization (locations were groundwater reacts with ultramafic rocks) influences the microbial communities. Many common characteristics were identified between sites including extremely basic, oxygen‐depleted, methane‐rich fluids. Aqua de Ney was found to be unique because no hydrogen (a product of serpentinization) was detected, it had an elevated concentration of sulfide. Methane at Aqua de Ney was determined to be formed through geologic reactions, while methane at The Cedars was partially created by microorganisms, and methane at the Tablelands was non‐microbial in origin. Knowing the range of geochemistry at these sites can help us understand the subsurface microbial communities that exist and the range of geochemistry they can tolerate. Key Points: CH4 from the Tablelands was non‐microbial and CH4 from The Cedars was a mixture of microbial and non‐microbial, supporting previous studies CH4 from Aqua de Ney Well was abiogenic in origin Despite being a product of serpentinization, no H2 was detected at Aqua de Ney, likely due to the formation of H2 S as well as abiogenic CH4